Inhibiting Pyridoxal Kinase of Entamoeba histolytica Is Lethal for This Pathogen - Devi, Suneeta; Tomar, Priya; Faisal Tarique, Khaja; Gourinath, Samudrala (Frontiers in Cellular and Infection Microbiology, 2021)
Pyridoxal 5’-phosphate (PLP) functions as a cofactor for hundreds of different enzymes that are crucial to the survival of microorganisms. PLP-dependent enzymes have been extensively characterized and proposed as drug targets in Entamoeba histolytica. This pathogen is unable to synthesize vitamin B6via de-novo pathway and relies on the uptake of vitamin B6 vitamers from the host which are then phosphorylated by the enzyme pyridoxal kinase to produce PLP, the active form of vitamin B6. Previous studies from our lab shows that EhPLK is essential for the survival and growth of this protozoan parasite and its active site differs significantly with respect to its human homologue making it a potential drug target. In-silico screening of EhPLK against small molecule libraries were performed and top five ranked molecules were shortlisted on the basis of docking scores. These compounds dock into the PLP binding site of the enzyme such that binding of these compounds hinders the binding of substrate. Of these five compounds, two compounds showed inhibitory activity with IC50 values between 100-250 μM when tested in-vitro. The effect of these compounds proved to be extremely lethal for Entamoeba trophozoites in cultured cells as the growth was hampered by 91.5% and 89.5% when grown in the presence of these compounds over the period of 72 hours.